Antimicrobial Peptides Aka Host Defense Peptides - From Basic Research to Therapy - Petrlova, Jitka (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue reprint will address the most current and innovative developments in the field of HDP research across a range of topics, such as structure and function analysis, modes of action, anti-microbial effects, cell and animal model systems, the discovery of novel host-defense peptides, and drug development.